2005
DOI: 10.1097/01.rct.0000165905.06031.b0
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly of the Portal Vein With Total Ramification of the Intrahepatic Portal Branches From the Right Umbilical Portion

Abstract: The possibility of this portal vein anomaly should be kept in mind when hepatic resection or partial liver transplantation is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The associated portal vein anomalies are significant in hepatectomy, split liver transplantation, or living donor liver hepatectomy in transplantation, and can be classified into three types: the trifurcation type, bifurcation type and the other type, in which portal vein ramification cannot be defined from conventional descriptions (Figure 6) [5,19] . Intrahepatic arteries in left-sided gallbladders have not previously been described in detail [2,5] .…”
Section: Discussionmentioning
confidence: 99%
“…The associated portal vein anomalies are significant in hepatectomy, split liver transplantation, or living donor liver hepatectomy in transplantation, and can be classified into three types: the trifurcation type, bifurcation type and the other type, in which portal vein ramification cannot be defined from conventional descriptions (Figure 6) [5,19] . Intrahepatic arteries in left-sided gallbladders have not previously been described in detail [2,5] .…”
Section: Discussionmentioning
confidence: 99%
“…Right‐sided ligamentum teres (RSLT) is a congenital anomaly in which the foetal umbilical vein is connected to the right paramedian trunk of the portal vein. The reported frequency of this anomaly ranges from 0.2% to 1.2% 1,2 and is known to accompany several intrahepatic vascular anomalies 1–7 . Several observational studies on the vascular architecture and embryologic origin of RSLT have been reported, 1–8 and reports of laparoscopic cholecystectomy or hepatectomy have been described.…”
Section: Introductionmentioning
confidence: 99%
“…15 This anomaly has been found in one in 192 individuals without the association with situs inversus, 15 and only a few cases have been reported. [15][16][17][18] This variation may lead to serious complications during major hepatic resection if not detected. 16 Additionally in the present case, the round ligament was terminated in this portion and was diagnosed as the "left" umbilical portion.…”
Section: Discussionmentioning
confidence: 98%
“…[15][16][17][18] This variation may lead to serious complications during major hepatic resection if not detected. 16 Additionally in the present case, the round ligament was terminated in this portion and was diagnosed as the "left" umbilical portion. Normally, in situs solitus, the right umbilical vein disappears in early fetal life, while remnants of the left umbilical vein remain to form the umbilical portion of the portal system, round ligament of liver, and Arantius ligament.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation